Fish consumption and dementia prevention in the elderly: Evaluating the "Dudu Galak" program in the coastal community of Bulak, Surabaya [Konsumsi ikan dan pengurangan risiko demensia pada lansia: Implementasi program "Dudu Galak" pada masyarakat pesisir Bulak, Surabaya] - Rachmawati, Kadek; Sukmanadi, M; Yudaniayanti, Ira Sari; Wurlina, W; Santoso, Kuncoro P.; Damayanti, Ratna; Putri, Desak Ketut Sekar Cempaka (Buletin Pengabdian, 2025)
In Indonesia, the elderly population is steadily increasing, and dementia is emerging as a significant public health concern. A lack of awareness regarding dementia prevention, particularly through nutrition-based interventions such as increased fish consumption, remains a major issue. This community service program aimed to educate fishermens wives and elderly residents by promoting the processing of fishery products, especially fish and shellfish, into various nutritious food products as a preventive measure against dementia. The program was implemented in Bulak, a coastal area of Surabaya, Indonesia, targeting fishermens wives and elderly community members through the Dudu Galak Program. The initiative focused on innovating the processing of local marine products into both dry and wet foods that are not only nutritionally rich but also economically valuable. The methods employed included educational outreach, hands-on training, and mentoring in the development of diverse, nutritious, and marketable seafood-based products. Additionally, the program provided education on dementia in older adults and strategies for its prevention. The results of this initiative demonstrated that fishermens wives and elderly residents successfully developed a variety of high-nutrition fish- and shellfish-based foods and snacks with promising market potential. Moreover, participants gained a better understanding of dementia and recognized that increasing fish consumption can serve as an effective preventive strategy. Through this program, it is expected that participants will improve their household income, enhance their knowledge of dementia, and promote greater fish consumption within fishing families as part of dementia prevention efforts among the elderly.